2017
DOI: 10.31227/osf.io/z7mab
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan

Abstract: Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh gaya kepemimpinan dan stres kerja terhadap kepuasan kerja karyawan pada PT. Utama Duta Harapan Makassar. Pengumpulan data menggunakan data primer yang di peroleh dari hasil penyebaran kuesioner. Populasi dalam penelitian ini adalah seluruh karyawan pada PT. Utama Duta Harapan Makassar yang berjumlah 110 orang karyawan tetap, Penentuan sampel dilakukan dengan menggunakan teknik stratified random sampling dengan menggunakan formulasi Slovin pada pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Based on the respondents' answers to leadership variable, although more people agree, it is necessary to pay close attention to the potential problems that arise. In line with the results of conducted by Amri et al reseach [8] and Hamsinah et al reseach [9], the partially there is a significant positive effect of leadership on employee job satisfaction. In the indicator the leadership can organize and direct you in carrying out your tasks, there are respondents who disagree with this statement.…”
Section: The Effect Of Leadership On Employee's Job Satisfaction At P...supporting
confidence: 85%
See 1 more Smart Citation
“…Based on the respondents' answers to leadership variable, although more people agree, it is necessary to pay close attention to the potential problems that arise. In line with the results of conducted by Amri et al reseach [8] and Hamsinah et al reseach [9], the partially there is a significant positive effect of leadership on employee job satisfaction. In the indicator the leadership can organize and direct you in carrying out your tasks, there are respondents who disagree with this statement.…”
Section: The Effect Of Leadership On Employee's Job Satisfaction At P...supporting
confidence: 85%
“…Leadership is the power to influence someone to do or not do something, for that leadership influences other parties and in realizing the stated organizational goals, [22]. [9] argue, there are indicators owned by leadership, which are as follows; 1) Ability to analyze and make decisions.…”
Section: Leadershipmentioning
confidence: 99%
“…From the research results. previously showed that there was a positive influence between Islamic leadership style on employee performance in an organization (Prayatna & Subudi, 2016).…”
Section: Discussion Variable Islamic Leadershipmentioning
confidence: 88%
“…The leadership applied to leaders varies according to needs so as to encourage subordinates to make the best contribution to the company, with effective leadership it can improve employee performance. (Prayatna & Subudi, 2016) His research shows several leadership styles as follows: autocratic, bureaucratic, charismatic, democratic, participative, situational, transactional and transformational.…”
Section: Islamic Leadershipmentioning
confidence: 99%
“…Customers who are satisfied with the product/service will plan to repeat the purchase. Based on several results of previous studies such as Haron et al (2020), Wijanarka et al (2015), Hamsinah et al (2014), andSatti et al (2020) state that customer satisfaction has a positive and significant effect on customer loyalty. In contrast to Pradana (2018) which states that customer satisfaction has a negative and insignificant effect on loyalty.…”
Section: Introductionmentioning
confidence: 96%